2009
DOI: 10.1021/bm900428q
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Amyloid Formation by Ionic Liquids: Ionic Liquids Affecting Intermediate Oligomers

Abstract: In searching for alternative ways to reduce or inhibit amyloid formation, we have studied this process using hen egg white lysozyme (HEWL) in the presence of a low concentration of protic ionic liquids. The ionic liquids were synthesized in a combinatorial fashion maintaining the cationic part (tetramethylguanidinium) with alteration of the anionic component of each compound tested. It was observed that one of these compounds (tetramethylguanidinium acetate) inhibited amyloid formation of HEWL in vitro by near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 56 publications
4
89
0
Order By: Relevance
“…Ionic liquids have attracted much interest recently as solvents for biomolecules because they are nonaqueous solvents that are able to promote the self-assembly of amphiphiles (29), and they appear to stabilize protein function (30,31), and some can promote, inhibit, or solubilize amyloid fibrils (32)(33)(34). To date, only high concentrations of strong acids such as formic acid and TFA have been reported to depolymerize rodlets to the monomeric form (6).…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids have attracted much interest recently as solvents for biomolecules because they are nonaqueous solvents that are able to promote the self-assembly of amphiphiles (29), and they appear to stabilize protein function (30,31), and some can promote, inhibit, or solubilize amyloid fibrils (32)(33)(34). To date, only high concentrations of strong acids such as formic acid and TFA have been reported to depolymerize rodlets to the monomeric form (6).…”
Section: Resultsmentioning
confidence: 99%
“…Tetramethylguinidium acetate decreased amyloid formation by nearly 50% in vitro, and led to thinner fibrils. 411 The conversion of Aβ monomers to Aβ amyloid fibrils was conducted in PIL−water solutions using the PILs consisting of the cations ethylammonium, diethylammonium, or triethylammonium paired with the methanesulfonate anion. 425 Increasing the substitution on the ammonium cation decreased the fibril formation, and it was suggested that this was due to differences in the hydrogenbonded network.…”
Section: Protein Stabilizationmentioning
confidence: 99%
“…20 One recent article on hen egg white lysozyme fibril formation in ionic liquids found no correlation with anion size/type, but the concentration used in the study was much lower than what is used typically to demonstrate Hofmeister effects. 21 …”
Section: 15mentioning
confidence: 99%